PENATALAKSANAAN RESTORASI KOMPOSIT KELAS IV DAN PASAK RICHMOND PASCA PERAWATAN SALURAN AKAR - I Gusti Ayu Fienna Novianthi Sidiartha; I Gede Marantika Yogananda Sutela (Interdental: Jurnal Kedokteran Gigi, 2020)
A 22-year-old male patient came to the Unud Hospital with complaints of 2 upper front teeth fractured. The patient complains pain in his upper right first incisor when he consumes cold beverages. Patient’s upper left lateral incisor felt spontaneous pain at first and had already been treated by a dentist, but the patient did not know the type of treatment he was receiving. The tooth now has never felt pain. Patients are now treated with mesial-distal class IV composite restorations in the upper right first incisor and endodontic treatment in the upper left lateral incisor continued by Richmond post, core and crown (PFM) restoration. One week evaluation after treatment showed the desired result which is the loss of subjective and objective complaints of the patient.